Research on Factors Influencing Traffic Capacity during Lane Closures on Inter-urban Expressways - SAKURAI, Mitsuaki; ONEYAMA, Hiroyuki; AOKI, Takashi; UEHATA, Junya (Journal of the Eastern Asia Society for Transportation Studies, 2024)
In recent years, there has been increased focus on the reconstruction, maintenance, and repair of bridges in Japan to ensure a safe and comfortable expressway space. These road works have often caused traffic congestion owing to lane closures. Setting an appropriate traffic capacity is essential to provide highly accurate prediction of traffic congestion and understand the factors that affect traffic. This study focuses on the breakdown flow rate (BDF) and queue discharge flow rate (QDF) as indicators of traffic capacity. Multiple regression analyses are performed to better understand the factors affecting traffic capacity of the construction lane closures implemented at the Tomei Expressway and Chuo Expressway, Japan, which are inter-urban expressways. A model is developed that includes not only known factors, such as nighttime and large-sized vehicle inclusion rate, but also new factors, such as traffic congestion involvement time and average spacing.